Comprehensive Review on Cervical Cancer: Global Health Burden - Aziz, Namra; Abbot, Vikrant; Bajpai, Aishwarya; Wal, Pranay; Wal, Ankita; Verma, Rakesh; Sharma, Mukesh Chandra (Current Cancer Therapy Reviews, 2025)
Cervical cancer is one of the four most common cancers that affect women worldwide, along with breast, colorectal, lung, and cervical cancer. It is a major public health concern that mostly affects women. Virtually all cases of cervical cancer are linked to human papillomavirus (HPV) infections. Patients must be screened and immunized to prevent this disease, although developed and developing nations have different rates of cervical cancer incidence. Palliative chemotherapy continues to be the go-to therapy for patients who are not candidates for radiation therapy or curative surgery. To counteract chemotherapy's low effectiveness, other treatment approaches are being developed. The main goals of this review study are to advance knowledge of cervical cancer, promote awareness and educated decision-making, and investigate cutting-edge approaches to the disease's treatment. A literature review was done from databases like Google Scholar, PUBMED-MEDLINE, and Scopus using standard keywords “Cancer,” “Cervical Cancer,” “Human papillomavirus,” “Chemotherapy,” and “Treatment Therapies” from 2010-2023. The Government of India intends to initiate a three-phase vaccination drive against Human Papillomavirus (HPV) for girls aged 9-14, aiming to mitigate the risk of cervical cancer. The vaccine also offers protection against the HPV strains that cause cancer of the anus, vagina, and oropharynx. Although cervical cancer is still a tough foe, we are getting closer to a time when it may be prevented and treated, even in the most underprivileged areas, due to continuous advancements and steadfast dedication.
Keywords: cervix